Intraoperative bone defect measurement in the acetabulum using a navigation system: The influence of bone porosity on the digitalization process. (September 2018) - Putzer, David; Scholl, Florian; Dankl, Lukas; Dammerer, Dietmar; Thaler, Martin; Nogler, Michael
Highlights: Digitalization of the acetabulum requires 1–4 min it could be used as an intraoperative bone defect measurement tool. Bone porosity has an impact on the digitalization of acetabular defects. Volume estimation within a 5% error of the theoretical calculated volume could be achieved. Abstract: The aim of the study was to evaluate how bone porosity affects intraoperative volume measurement of the acetabulum in a plastic bone model study and to validate the measurement method on cadaveric acetabula. Point cloud collection was performed using a navigation system and compared to CT measurements as well as theoretical calculations on sawbones with different porosities and validated on cadaveric specimens. The grade of porosity had a significant influence on the volume measurement. In high porous materials volume calculation (61.5 cm²) was overestimated when using a digitalizer, while in materials with low porosity the volume was underestimated (57.0 cm²) in comparison to the known size of the defect (59.4 cm²). Digitalization time of the acetabulum was between 1 and 4 min. Validating the measurement on cadaveric bones no statistical significant difference could be found between digitalized volumes and theoretically calculated volumes. As digitalization of the acetabulum can be carried out in a reasonable time it could be used as a measurement tool to estimate the amount of allografts needed for filling bone defects.